Study on Seroprevalence and Leptospiral Antibody Distribution Among Livestock Breeders and Farmers in Golestan Province - Malihe Naderi; Vahideh Hamidi Sofiani; Reza Hoseinpour; Amir Mohammad Alborzi; Seyed Amir Soltani (Veterinary Medicine and Science)
ABSTRACT Background The high prevalence of leptospirosis in humans is of great public health concern, particularly in tropical and subtropical regions. Objective This study aimed to determine the seroprevalence of leptospiral antibodies and the distribution of serovars in livestock breeders and farmers in Golestan province. Methods Seventy samples of serum collected from farmers and ranchers suspected of leptospirosis were examined using an ELISA method for surveying Immunoglobulin M (IgM) anti‐leptospiria. Also from samples, DNA was extracted and PCR was performed using by primers for 16s rRNA. Demographic properties of positive patients were analysed. Results Chi‐square statistical test shows a statistically significant difference between the gender and prevalence leptospirosis (p‐value = 0.004). Also, by examining the age, it was shown that 68.57% of patients are in the middleaged rang. According to the results obtained from the study and investigation of blood serum IgM‐and Immunoglobulin G (IgG) in people suspected of leptospirosis, 3 cases of the patients had IgM higher than 11 and were known to be positive for leptospirosis. Also, by examining the IgG level of patients, 5 cases had intermediate results, and 2 cases were found to be positive for IgG. The PCR results showed that 41.42% of patients tested positive for the 16s rRNA. Conclusion Leptospirosis is a common disease among farmers, and in Golestan province, considering traditional farming methods, it is considered an important infectious disease. Therefore, health and safety measures should be expanded to control and prevent this disease. Also, by employing mechanised agricultural methods, the prevalence of leptospirosis in this region can be significantly reduced.